PERAN GURU DALAM MEMOTIVASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA KELAS V SD NEGERI KALIDERES 05 PAGI JAKARTA BARAT - Robiatul Adawiyah; Ina Magdalena; Asep Taufiqurrahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is entitled The Role of Teachers in Motivating Learners in Learning Mathematics Class V SD Negeri Kalideres 05 Pagi West Jakarta, the purpose of this research is to find out the role of teachers in motivating student learning in learning mathematics class V SD Negeri Kalideres 05 Pagi West Jakarta. This research uses descriptive qualitative research. The subjects of this study were 1 teacher, 2 students, and 1 parent of grade V students. This research was conducted at SD Negeri Kalideres 05 Pagi West Jakarta. The data collection techniques used in this study were observation of the role of teachers and students' learning motivation, then interviewing 1 teacher, 2 students, and 1 parent, and supported by documentation. The results of the research conducted show that the role of the teacher in motivating students' learning has basically tried to carry out its role to arouse students' learning motivation by providing encouragement in the form of praise and encouraging words to students. However, the way teachers provide motivation is not enough to generate motivation to learn mathematics.